Mobilization to revolution: stakeholders’ perception of Omoyele Sowore's #revolutionnow campaigns in Nigeria (2021)
The study investigated stakeholders' perception of Omoyele Sowore's #RevolutionNow campaigns in Nigeria. The multistage sampling procedure was adopted. First stage, simple sampling technique was used to select three local governments each from the senatorial districts of Ondo State namely Owo (Ondo North), Ondo (Ondo Central) and Irele (Ondo South). In the second stage, the purposive sample technique was used to select 50 stakeholders with two main criteria of age (above 50 years old and above) and must have voted in the last two generation elections (2015 and 2019). A self-designed instrument titled Stakeholders' Perception of Omoyele Sowore URevolution Now (r=0.82) and Structured interview guide (S1G) were used. Data were analysed using descriptive statistics, while qualitative data were content-analysed. The findings show that stakeholders have moderate perception of Omoyele Sowore's URevolution Now campaigns but with the understanding that it is a needless gesture. It is also discovered that there are several alternatives to revolution which can be subscribed to in a country like Nigeria. Thus, the study recommended the need for more awareness of the imports of joining Omoyele Sowore's Revolution Now campaigns as well as the need to adopt new strategies as suggested by stakeholders for the Nigerian project.